Detection of Plasmodium vivax in a child returning from India by use of broad-range PCR and electrospray ionization mass spectrometry - Rounds, Megan A (Nature Publishing Group, 2012)
Plasmodium vivax is a common cause of imported malaria in the USA, second only to P. falciparum. We present a case of P. vivax malaria in a child returning from India. P. vivax was initially diagnosed by standard methodology and detected retrospectively by use of broad-range PCR and electrospray ionization mass spectrometry using a panel of primers designed to detect vector-borne pathogens. This is the first reported case of P. vivax detection using PCR and electrospray ionization mass spectrometry.